Cosmic Microwave background bispectrum from Active Models of Structure Formation - Gangui, Alejandro (2001)
We propose a method for a numerical computation of the angular bispectrum of the cosmic microwave background (CMB) anisotropies arising from active models such as cosmic topological defects, using a modified Boltzmann code based on CMBFAST. The method does not use CMB sky maps and requires moderate computational power. As a first implementation, we apply our method to a recently proposed model of simulated cosmic strings and estimate the observability of the non-Gaussian bispectrum signal. A comparison with the cosmic variance of the bispectrum estimator shows that the bispectrum for the simulated string model we used is not observable.